Methyl Ester Production From Vegetable Oils on Heterogeneous Basic Catalysts - Umdu, Emin Selahattin; Şeker, Erol (Izmir Institute of Technology, 2008)
In this study, the activities of heterogeneous mixed oxide catalysts; magnesium and calcium oxide on alumina and silica supports were investigated for transesterification of vegetable oils; canola and sunflower, to methyl esters. The primary objective of this study is to understand whether basicity of the solid catalysts and/or its crystallite size affect the biodiesel yield during the reaction. The mixed oxide catalysts were prepared by a single step sol-gel method. Magnesium oxide (MgO) and calcium oxide (CaO) were chosen because of their basic property.This study shows that the crystallite size does not have any direct effect on the transesterification activity. Yet, the interaction of the crystallites with the support material may change the number of the active sites and/or the creation of new .basic. sites. In fact, the basicity was found as the critical factor for the choice of the suitable mixed oxide for the transesterification reaction. The addition of CaO to alumina creates synergetic effect. But this is not observed with the catalysts: CaO/SiO2 and also the MgO/Al2O3 and MgO/SiO2.CaO/Al2O3 differs from the others in such a way that it contains the basic sites with the mild basic strength. Not only the crystallite size but also the type of the oxide is important to obtain the heterogeneous catalysts as active as the homogeneous catalyst. CaO/Al2O3 has the same activity as that of NaOH for the transesterification of canola and sunflower oils at 50 oC. It was also found that the activity of CaO/Al2O3 was truly heterogeneous.
Thesis (Master)--Izmir Institute of Technology, Chemical Engineering, Izmir, 2008
Includes bibliographical references (leaves: 40-43)
Text in English; Abstract: Turkish and English
viii, 43 leaves
Keywords: QD341.H9 U49 2008; Methyl groups; Esters; Vegetable oils; Heterogeneous catalysis